CPW‐to‐SL transition in LTCC technology. Issue 9 (1st April 2017) - Bhutani, A.; Goettel, B.; Thelemann, T.; Zwick, T.
Abstract : A coplanar waveguide (CPW)‐to‐stripline (SL) via‐based signal transition operating from DC to 150 GHz is presented. The signal transition is manufactured using low‐temperature co‐fired ceramic (LTCC) technology and it is the largest‐bandwidth LTCC vertical signal transition published to date, according to the best of the authors' knowledge. Probe‐based S ‐parameter measurements of the transition show that the single‐ended CPW‐to‐SL signal transition has below 1 dB insertion loss for frequencies up to 150 GHz, thereby demonstrating it as a suitable component for realisation of a low‐cost, fully integrated, surface‐mountable millimetre‐wave system‐in‐package.